Manufacturing Process Changes and Reduced Skin Irritations of an Adhesive Patch Used for Continuous Glucose Monitoring Devices. (May 2018) - Gisin, Vitaliy; Chan, Anna; Welsh, John B.
Adhesives used for continuous glucose monitoring (CGM) devices can cause skin irritations, which sometimes lead to abandonment of the therapy. A previous sensor manufacturing process involved two separate adhesives—one applied to the skin-facing surface of the fabric patch, and a second, ethyl cyanoacrylate-based adhesive, which secured the plastic transmitter housing to the superficial side of the patch. Our current process for attaching the transmitter housing to the fabric patch uses heatstaking, wherein the housing is heated and pressed against the patch with a specialized assembly apparatus. Heatstaking simplifies the sensor assembly process and obviates the need for the second adhesive, which may lead to lower risk of skin irritation(s) in some patients.